A New control structure for tert-amyl methyl ether production using reactive distillation. (February 2020) - Kharaji, Shahin; Sadeghi, Jafar; Shahraki, Farhad; Khalilipour, Mir Mohammad
Abstract: The aim of this paper is to introduce new control structures in both centralized and decentralized scheme for tert-amyl methyl ether (TAME) production unit using reactive distillation which developed as a benchmark by Luyben (2005). Steady state and dynamic simulation was performed based on the case study data using Aspen® simulator. Dynamic simulation shows that control performance of the plant has oscillatory behavior using conventional PI controllers. Hence, a proper modification on the process flow sheet was carried out in order to remove oscillatory behavior of the process. Although, the new structure has better dynamic performance than the previous one using PI controller, it is not capable of eliminating the oscillations completely. Non-minimal state space with proportional integral plus controller (NMSS–PIP) controller was applied to dynamic model of the modified process. In this way, the system identification was carried out using refined instrumental variable (RIV) method and state matrices was obtained as left matrix fraction description (LMFD). The control performance of the PI and PIP controller for the modified structure revealed that the NMSS–PIP, completely eliminates the process oscillations while it has smoother responses with better settling time than the PI configuration. Furthermore, comparison of the ITAE criterion between main case and modified process indicates that the ITAE for PI and PIP control decreased by about 20% and 88%, respectively. Highlights: The control performance of TAME process improved by process flowsheet modification. A new centralized plant-wide control using NMSS–PIP presented for TAME process.